PENGEMBANGAN BAHAN AJAR PRAKTIKUM AKUNTANSI BERBASIS PEMBELAJARAN KOLABORATIF - Edutivia Mardetini; Siti Fatimah; Dian Eka Amrina (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
The problem formulated is how the validity, and practicality of practical colaborative teaching-based accounting practice. As for the purpose of this study is to describe the level of validity, and practicality of materials accounting practice course -based collaborativelearning. This type of research is Research & Development (R & D) by Borg & Gall. Population in this study all students of economic education academic year 2017-2018. The sample of research that is students Indralaya class which take Accounting Practice course that amounts to 45 students. Data collection techniques used were questionnaires and tests of learning outcomes. With a validity test 91.67% obtained from the material experts and 90% of linguists who showed the results of both valid categorized vallidators. Then from the test practically obtained results stating that this resource is practically used to understand the material of accounting practice. Thus the development of cooperative learning materials based on collaborative learning accounting is valid and practical use in lectures activities.